Uterine Didelphys with Pregnancy Outcomes: A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
A didelphys uterus also known as a “double uterus” is one of the least common Mullerian duct anomalies. Uterine didelphys is a congenital malformation that result from complete failure of fusion of the ipsilateral Mullerian duct during embryonic development. Ideally, diagnosis should be made before pregnancy and labour to prevent adverse outcomes. Here reporting a case who was a 19 years old, 4thgravida, Para: 0+3 (Spontaneous abortion) referred to Bangabandhu Memorial Hospital (BBMH) USTC, Chittagong at 35 weeks of pregnancy with severe abdominal pain by local physician from Raozan, Chittagong. On vaginal examination a longitudinal vaginal septum and two vagina were found. Uterine Didelphys was confirmed during emergency caesarean section and delivered 1.5 kg male baby with APGAR score 7/10 and was referred to Neonatal Intensive Care Unit (NICU). Post operative recovery of the mother was uneventful. The baby was also discharged at the age of seven days with establishment of breast feeding. To avoid delayed diagnosis and associated adverse outcome clinicians should have high index of suspicion of uterine anomaly when assessing cases of dysfunctional labour.Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 53-55